Insulative trousers incorporating active heating reduce muscle temperature decline following warm up and improve sprint cycling performance - Faulkner, S.; Ferguson, R. A.; Gerrett, N.; Hodder, S. G.; Hupperets, M.; Havenith, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Elevations in muscle temperature (Tm) have been shown to be important for enhancing maximal muscle power output during short duration, sprint based activities, hence the completion of a warm up prior to many exercise types. In many sporting competitions it is not uncommon for there to be delays between warm up completion and performance execution, during which time activity levels may be insufficient to maintain elevations in Tm. Excessive decline in Tm may lead to sub-optimal contractile conditions and impaired exercise performance. Therefore, the aim of the present study was to determine to what extent a delay between warm up and competition might influence Tm and performance and whether this may be attenuated using an insulated athletic trouser with optional heating. METHODS: On three separate occasions, 11 male cyclists (24 ± 5yrs; 182.4 ± 7.6cm; 77.4 ± 10.0kg) completed a standardized 15 min intermittent sprint-based warm up on a cycle ergometer, followed by a 30 min passive recovery period before completing a 30 sec maximal sprint test. Tm of the vastus lateralis was measured at depths of 1, 2 and 3 cm prior to and following the warm up and immediately before the sprint test. Measures of absolute and relative peak power output were taken. During the recovery period subjects wore a tracksuit top and (in a balanced order) either i) a standard tracksuit ensemble (CONT), ii) a pair of insulated athletic trousers (INS) or iii) insulated athletics trouser with inbuilt electric heating elements around the thighs (HEAT). RESULTS: The warm up increased Tm at all depths by ~2.5°C, with no differences between conditions. Following the recovery period Tm declined in both CONT (1cm 36.3 ± 0.4°C; 2cm 36.6 ± 0.3°C; 3cm 36.9 ± 0.2°C) and INS (1cm 36.5 ± 0.6°C; 2cm 36.8 ± 0.4°C; 3cm 37.0 ± 0.3°C), whereas Tm for HEAT remained elevated at all depths compared to both INS and CONT (1cm 37.4 ± 0.3°C; 2cm 37.3 ± 0.2°C; 3cm 37.3 ± 0.2°C; p<0.01). Peak power output was higher in HEAT (20.9 ± 1.6 W/kg) than both CONT (19.2 ± 1.7 W/Kg; 9%, p<0.05) and INS (20.3 ± 2.3 W/Kg; 3%, p<0.05). DISCUSSION: Though insulated trousers alone were not effective, the use of an insulated athletic trouser with the addition of electric heating elements around the thighs was able to reduce the decline in Tm that is associated with forced periods of inactivity between warm up completion and competition. Furthermore, the prevention of the decline in Tm improved subsequent sprint performance compared to when passive heating is not used.